2022
DOI: 10.1101/2022.02.07.479475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Building an atlas of transposable elements reveals the extensive roles of young SINE in gene regulation, genetic diversity, and complex traits in pigs

Abstract: Transposable elements (TEs) are an extensive source of genetic polymorphisms and play an indispensable role in chromatin architecture, transcriptional regulatory networks, and genomic evolution. The pig is an important source of animal protein and serves as a biomedical model for humans, yet the functional role of TEs in pigs and their contributions to complex traits are largely unknown. Here, we built a comprehensive catalog of TEs (n = 3,087,929) in pigs by a newly developed pipeline. Through integrating mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 117 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…The effects of TE on gene regulation are also reflected in the 3D chromatin structure, chromatin accessibility, histone modification, and transcription factor binding site (TFBS) [ 47 ]. It is worth noting that the age of TE is a key factor that affects their activity and tolerance in the pig genome [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of TE on gene regulation are also reflected in the 3D chromatin structure, chromatin accessibility, histone modification, and transcription factor binding site (TFBS) [ 47 ]. It is worth noting that the age of TE is a key factor that affects their activity and tolerance in the pig genome [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…We first detected 211,067 polymorphic SINE at the population level using 374 next-generation sequencing (NGS) data. Based on this, we found that TE can clearly recapitulate known patterns of population admixture in pigs [ 48 ].…”
Section: Introductionmentioning
confidence: 99%